Aesthetic medicine treatments in terms of patient rights (Journal of Face Aesthetics, 2020)
Treatments in the field of facial aesthetic medicine are largely related to the discontinuity of the skin and are performed by both doctors and dentists. In the dentist's office, where such procedures are performed, as in any other therapeutic entity, the patient's rights apply, which are a guarantee of subjective treatment of the patient. They enable the patient in the situation of violation of patient's rights, dissatisfaction with the effects or occurrence of a complication or adverse event to refer the case to the appropriate authorities. The paper presents the basic rights of the patient, expressing the protection of his autonomy (freedom of will, awareness and knowledge) in terms of his own health.
Keywords: patient's rights; aesthetic medicine; doctors; dentists